Peran Artificial Intelligence (AI) dalam Meningkatkan Layanan Pendidikan di SMP/MTs - Abdul Kodir, (Manajemen Kreatif Jurnal, 2025)
This research explores the role of Artificial Intelligence (AI) in improving education services at the junior high school and madrasah Tsanawiyah (MTs) levels. AI technology contributes significantly to learning personalization, student data analysis, and school administration efficiency. Through the Narrative Literature Review method, this research analyzes various literatures to identify the impact of AI on education, including challenges and potential solutions. The results show that AI supports more adaptive learning by analyzing students' individual needs, providing data-driven recommendations, and accelerating decision-making in the education process. In addition, AI improves operational efficiency through the automation of administrative tasks, such as managing student attendance and grades. However, AI implementation faces challenges such as limited infrastructure, lack of technical training for teachers, and data privacy issues. With strategic investment and intensive training, AI technology has great potential to revolutionize the education system, creating an inclusive and sustainable learning ecosystem.